1998
DOI: 10.1111/j.1348-0421.1998.tb02351.x
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Gene Expression of Subacute Sclerosing Panencephalitis (SSPE) Virus (Osaka‐1 Strain): A Comparison of Two Sibling Viruses Isolated from Different Lobes of an SSPE Brain

Abstract: The Fr/V and Oc/V sibling viruses of the Osaka-1 strain of the subacute sclerosing panencephalitis (SSPE) virus were defective in cell-free virus production. By radioimmunoprecipitation assay, the matrix (M) protein was not detected in cells persistently infected with the Osaka-1 strain. This undetectable expression was consistent with the selective reduction of antibody response to the M protein in the patient from whom the Osaka-1 strain was isolated. The sequence of the M gene, however, predicted that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In many SSPE strains, an A-to-Gbiased hypermutation occurred in the genome and destroyed the M protein-coding frames. In some cases, translation of the M protein is complicated by a transcriptional defect that leads to an almost exclusive synthesis of dicistronic P-M mRNA (4,12,13,61). Elucidation of the mechanism of the aberrant read-through transcription at the P-M gene junction revealed that a single deletion or mutation at the P gene end was responsible (5).…”
Section: Measles Virus (Mv) Is the Causative Agent For Acute Measles mentioning
confidence: 99%
See 1 more Smart Citation
“…In many SSPE strains, an A-to-Gbiased hypermutation occurred in the genome and destroyed the M protein-coding frames. In some cases, translation of the M protein is complicated by a transcriptional defect that leads to an almost exclusive synthesis of dicistronic P-M mRNA (4,12,13,61). Elucidation of the mechanism of the aberrant read-through transcription at the P-M gene junction revealed that a single deletion or mutation at the P gene end was responsible (5).…”
Section: Measles Virus (Mv) Is the Causative Agent For Acute Measles mentioning
confidence: 99%
“…Plasmids encoding chimeric F proteins, OSA2-ext and OSA2-cyt, were previously described as Osa2/Toy and Mas/Osa2, respectively (6). The nucleotide sequences of the M, F, and H genes of the Osaka-2 strain were reported previously (4,23,47). Plasmids encoding mutant F proteins were constructed by a PCR-based method with synthetic primer pairs, and the inserts were confirmed by sequencing.…”
Section: Cells and Viruses Cho Cells Expressing Cd46 (Cho/cd46) Cellmentioning
confidence: 99%
“…A similar transcriptional alteration at the P-M gene junction of the MF strain of SSPE virus also has been reported (12). The P-M dicistronic RNA product has also been detected in cells infected with the Osaka-1 strain or with one of the sibling viruses of the Osaka-2 strain (1,34). In addition, the transcriptional patterns for the P and M genes differed from lot to lot of the Yamagata-1 strain (our unpublished observation).…”
mentioning
confidence: 71%
“…The mutation rates of each viral protein-coding region range from 0.8% (L coding region) to 1.6% (H coding region), with the overall mutation rate being 1.2% (194/15,894) ( Table 2). It has been reported that the M gene of SSPE virus possesses a considerably large number of mutations (usually more than 30), the majority of which are the U-to-C biased hypermutation (2,9,20,45). We found that the mutation rate of the M coding region of SSPE-Kobe-1 was only 1.2% (12/1,008).…”
Section: Nucleotide Sequence and Phylogenetic Analyses Of The Sspe VImentioning
confidence: 99%